UJI AKTIVITAS ENZIM PROTEASE DARI ISOLAT Bacillus sp. GALUR LOKAL RIAU - Rani Yuniati; Titania Tjandrawati Nugroho; Fifi Puspita (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Proteolytic bacteria are bacteria that are able to hydrolize proteins into smaller peptides or completely into amino acid units. This study was carried out to determine the proteolytic activity of Bacillus sp. B1 isolated from rhizosphere of mustard plants. The proteolytic activity of the enzymes were determined based on the amount of tyrosin liberated in Unit/mL, while the specific activity of the enzymes were indicated by activity per unit weight of proteins. The protein concentration of enzyme extracts were determined by the Lowry method. The activity of enzyme was determined at various production times (6, 12, 18, 24, 30, and 36 hours). The results showed that the Bacillus sp. B1 isolate was able to produce protease. Bacillus sp. B1 isolate obtained its maximum activity in 30 hours of production time. The specific activity of protease Bacillus sp. B1 was 0,2523 ± 0,0050 Unit/mg proteins.Proteolytic bacteria are bacteria that are able to hydrolize proteins into smaller peptides or completely into amino acid units. This study was carried out to determine the proteolytic activity of Bacillus sp. B1 isolated from rhizosphere of mustard plants. Theproteolytic activity of the enzymes were determined based on the amount of tyrosin liberated in Unit/mL, while the specific activity of the enzymes were indicated by activity per unit weight of proteins. The protein concentration of enzyme extracts were determined by the Lowry method. The activity of enzyme was determined at various production times (6, 12, 18, 24, 30, and 36 hours). The results showed that the Bacillus sp. B1 isolate was able to produce protease. Bacillus sp. B1 isolate obtained itsmaximum activity in 30 hours of production time. The specific activity of protease Bacillus sp. B1 was 0,2523 ± 0,0050 Unit/mg proteins.